Problems of developing an expert system for industrial fish farming under martial law conditions - Дацишин, Сергій; Мічута, Ольга (Modeling, Control and Information Technologies: Proceedings of International scientific and practical conference, 2025)
The article addresses the main challenges faced by the industrial fish farming sector in Ukraine during wartime. Military actions negatively impact the infrastructure and personnel of fish farms, causing issues with supply chains, logistics, qualified personnel, and the environmental condition of water bodies. The author emphasizes the difficulties in maintaining stable operations of enterprises, particularly due to economic factors such as reduced investments, increased tax burden, and rising production costs. The article proposes steps to mitigate these challenges, including the creation of wintering ponds, the breeding of in-house stocking material, reducing the number of fish stock to maintain ecological balance, and focusing on herbivorous fish species and catfish that are less dependent on purchased feed У статті розглянуто основні виклики, з якими стикається галузь промислового риборозведення в Україні в умовах війни. Військові дії негативно впливають на інфраструктуру та персонал рибних господарств, створюючи проблеми з постачанням, логістикою, кваліфікованим персоналом та екологічним станом водойм. Автор акцентує увагу на складнощах у підтримці стабільної роботи підприємств, зокрема через економічні фактори, такі як зменшення інвестицій, збільшення податкового навантаження та собівартості продукції. Запропоновано кроки для пом'якшення цих викликів, включаючи створення зимувальних ставків, розведення власного посадкового матеріалу, зменшення кількості посадкового матеріалу для екологічного балансу та орієнтацію на вирощування рослиноїдних риб і сомів, які менш залежні від закуплених кормів.